Analisis Bisnis Model Canvas pada Cafe Lawu Break Coffe and Nongki Tawangmangu - Djong, Alexander Mario Retto (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
This research uses a Business Model Canvas evaluation which aims to develop a business model at Cafe Lawu Break Tawangmangu which starts from the identification process then continues with a SWOT analysis of the nine elements of the Business Model Canvas. This research uses qualitative descriptive analysis with data collection techniques using in-depth interviews and testing the validity of the data by source triangulation. The results of the analysis carried out show that several elements of the business model can be improved and developed even better. Cafe Lawu Break has a clear value proposition, namely by providing good quality food and beverage services at friendly prices. However, the competition for a cafe or restaurant is so tight that it requires looking for various alternative ways to develop its business model so that it can continue to compete and be an option. 24-hour operational hours and other after-sales services can be provided to customers. It is necessary to use technological aspects in the purchase ordering system, such as using the Gofood, Grabfood or WA business applications and maximizing social media. It is also possible to use QRIS technology in ordering. Expansion of the business area for consumer capacity and vehicle parking is required. Cafe Lawu Break can also look at other market opportunities, such as serving meal package sales for both home and office scale.